2017
DOI: 10.1016/j.aap.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

In search of the severity dimension of traffic events: Extended Delta-V as a traffic conflict indicator

Abstract: Most existing traffic conflict indicators do not sufficiently take into account the severity of the injuries resulting from a collision had it occurred. Thus far, most of the indicators that have been developed express the severity of a traffic encounter as their proximity to a collision in terms of time or space. This paper presents the theoretical framework and the first implementation of Extended Delta-V as a measure of traffic conflict severity in site-based observations. It is derived from the concept of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 28 publications
2
91
0
Order By: Relevance
“…It can be stated that the ∆V parameter represents the most reliable surrogate safety indicator according to this work. This result is in accordance with recent studies that have proposed an evolution from traditional traffic safety indicators that can be obtained from SSAM software [20]. This new direction of research suggests, in fact, the use of indicators that consider the severity of potential crashes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It can be stated that the ∆V parameter represents the most reliable surrogate safety indicator according to this work. This result is in accordance with recent studies that have proposed an evolution from traditional traffic safety indicators that can be obtained from SSAM software [20]. This new direction of research suggests, in fact, the use of indicators that consider the severity of potential crashes.…”
Section: Discussionsupporting
confidence: 91%
“…In case study 1, the parameters that showed better correlation (both of Pearson [20] and of Spearman [47]) turn out to be ∆V total and collision; instead, in case study 2, the parameters that are best correlated to the real data are those related to the number of deaths and the number of injuries. This stems from the fact that the area of Paseo de Pereda is an urban area where vehicles are very close to each other.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Some of the original traffic conflict techniques attempt to combine these two severity dimensions by having some subjective score set by an observer. Recently, some objective indicators have been proposed for the same purpose (Alhajyaseen 2015;Bagdadi 2013;Laureshyn et al 2017).…”
Section: Surrogates Safety Measuresmentioning
confidence: 99%